DAMPAK KEBIJAKAN EKONOMI INTERNASIONAL TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Teuku Mohammad Daffa Al Islami; Maulana Ash Shiddiqi Bayu Pamungkas; Muhamad Abdan Zulfa; Achmad Yandra Prasetio; Sarpini Sarpini (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This article examines the effect of international economic policy on Indonesia's economic growth. The background to this research indicates that globalization and international trade play an important role in the economic development of a country. The aim of this research is to evaluate the influence of trade policies, payments and foreign aid on economic growth in Indonesia. The method applied is a literature review, which involves comparison and analysis of various relevant policy theories and practices. Research findings show that international economic policies have had positive impacts, including increasing exports, job creation, and increasing national income. However, there are challenges such as protectionism and dependence on imports that need to be considered. This research recommends the importance of more responsive policies to maximize the benefits of international trade.